Comparative study on traditional and modern mosques’ design, construction and community participation: case study in Peninsular Malaysia / Ilyana Sujak - Sujak, Ilyana (2014)
In the last few decades, building construction industry in most Muslim countries has had to keep pace with the modem method of construction and technology development. Malaysian mosques architecture is not exempted from the physical conversion of this promptly changing technology. Therefore, this research attempts to discover the transformation of mosque building from traditional to modem architecture in Peninsular Malaysia. It analyzes and compares the design, construction and community participation of the case study mosques. It intends to discover the differences of mosque building in two different periods of time. The overview of literature includes the published and unpublished sources on mosque; definition of mosque from the Qur’an and scholars; universal elements of mosque architecture; design, construction and community participation in traditional and modem architecture and Malaysian mosques. Literature written on mosques is extensive but only few address this topic. The case study method is employed, measurements comprising: on-site physical measurement, on-site observation and interview session with expert informant. Measured and detail drawings reproduction by Computer Aided Design application of the case studies and tabulations of data were prepared for the final data analysis. Various findings are revealed in this study on the comparison of traditional and modem mosques construction. The findings from this research conclude that there are significant numbers of differences found between the traditional and modem mosques in the aspect of design, construction and community participation. The research hopes to enrich the understanding of the traditional and modem mosques architecture with specific scope on construction.